IN VITRO ANTIMICROBIAL EFFECT OF OXYCLOZANIDE ANTHELMINTIC AGAINST DRUG RESISTANT STAPHYLOCOCCUS AUREUS ISOLATED FROM BOVINE MASTITIS MILK - A. Elamaran; P. Senthil Kumar; V. Ranganathan; K. Kannan; T. Ramasamy; C.M. Jaikanth; S. Senthil Kumar; J. Vijay Anand (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study investigated oxyclozanide, a salicylanilide anthelmintic, as an alternative treatment for Methicillin-resistant Staphylococcus aureus (MRSA) in bovine mastitis. With conventional treatments facing challenges due to antibiotic resistance, oxyclozanide demonstrated promising in vitro antimicrobial effect against MRSA isolates. The minimal inhibitory concentration (MIC) ranged from 0.5 to 1.0 μg/ml, indicating its efficacy. Oxyclozanide’s mechanism involved disrupting the transmembrane structure of bacteria, presenting a potential strategy against MRSA. This suggested the repurposing of oxyclozanide as a viable option for combating MRSA in bovine mastitis, prompting further investigation into its precise mechanism and therapeutic potential.